Productive and Reproductive Performance of Indigenous Chickens in Ethiopia - Milkias, Matawork (International Journal of Scientific Research in Civil Engineering, 2017)
This study reviews the productive and reproductive performance of indigenous chickens in Ethiopia with the aim of delivering summarized and synthesized information for the beneficiaries and producers. Chicken production is encompasses into traditional scavenging, small and large-scale market orientated systems based on the objective of the producer, the type of inputs used and the number and types of chickens kept. In Ethiopia, indigenous chickens produces 10-20 eggs per clutch and 30-65 small eggs per hen per year in 3-4 clutches. Local chickens reach slaughter/market age at 8 to 12 months with 0.6-2.5kg average weight at farmer management system. Indigenous chickens require long time to reach sexual maturity and takes longest time to recover reproductive cycle by local broody hen. The average mortality rate was highest and which affects both productive and reproductive performance of indigenous chickens by reducing survival rate. There were huge number of indigenous chickens existing in Ethiopia but productivity was disproportional to the number of chickens. The major constraint which affects productive and reproductive performance of indigenous chickens are diseases and predators, feed shortages, lack of training and extension services, and lack of proper marketing systems. In conclusion, lowest productive and reproductive performance was recorded which needs further improvement by adjusting training and extension service for farmers.